Serum creatinine and albumin predict sarcoma‐specific survival in patients with myofibroblastic and fibroblastic sarcomas. Issue 12 (6th June 2017) - Willegger, Madeleine; Posch, Florian; Schieder, Sophie; Funovics, Philipp Theodor; Scharrer, Anke; Brodowicz, Thomas; Ay, Cihan; Windhager, Reinhard; Panotopoulos, Joannis
ABSTRACT: Recent evidence suggests that common prognostic factors predicting disease progression and survival in soft tissue sarcomas (STS) are not applicable to all STS entities, indicating the need for histotype specific evaluation of new prognosticators. This study aimed at evaluating preoperative serum creatinine, albumin, and the albumin‐creatinine ratio (ACR) as markers for survival in patients with malignant fibroblastic and myofibroblastic sarcomas. One hundred and thirty‐two patients who underwent sarcoma resection have been included. Statistical analysis comprised uni‐ and multivariable Cox proportional hazard models, competing risk analysis and Kaplan–Meier estimates. The 5‐year overall survival (OS) was estimated at 64.1% (95%CI: 53.7–72.8) and the 5‐year sarcoma‐specific mortality was 19.9% (95%CI: 12.8–28.1). Elevated serum creatinine levels were significantly associated with an impaired sarcoma‐specific survival (SSS) adjusted for tumor stage (subdistribution hazard ratio (SHR) per 1 mg/dl increase: 3.27; 95%CI: 1.87–5.73; p  < 0.0001). Low serum albumin levels were associated with a shorter recurrence‐free survival (RFS) experience (HR per 10 g/L increase: 0.62; 95%CI: 0.41–0.94; p  = 0.024). The ACR emerged as an AJCC‐stage‐independent prognosticator of SSS (SHR per 1 unit increase: 0.94; 95%CI: 0.90–0.98; p   =  0.003). In conclusion, serum albumin and creatinine have been confirmed as predictive biomarkers for disease‐specific outcomes in myofibroblastic and fibroblastic sarcomas. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2815–2824, 2017.